GEOVAN PSIMAT Setting Fun Gratitude Activities for Kids: An Alternative Learning Model for Disaster Emergency Response - Amrul Aysar Ahsan; Lisa Aditya Dwiwansyah Musa; Nur Mawakhira Yusuf; Annisa Dewi Ayu Tri Ambarwati; Amanda Puspita (Universitas PGRI Yogyakarta, 2026)
This study aims to develop a learning model in emergency response situations using the GEOVAN PSIMAT setting, fun gratitude activities. This learning model combines the concepts of geometry and child psychology, using a fun approach and teaching children gratitude. This model is designed to improve mathematical understanding while reducing stress and psychological trauma in children affected by disasters. This research is a development study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), covering the analysis, design, and development stages. The GEOVAN PSIMAT model makes an original contribution by integrating a positive psychology approach grounded in gratitude, contextual emergency learning, and child-friendly psychosocial interventions into a single operational framework applicable during the disaster emergency response phase. Previous studies show that disaster education and learning in emergency situations are generally still positioned sectorally, i.e., limited to increasing preparedness knowledge, disaster simulations, or psychosocial recovery, all separate from the academic learning process. The analysis results indicate that mathematics learning in emergency situations should be simple, flexible, activity-based, and integrated with emotional management activities, particularly gratitude activities. The validation results show that the GEOVAN PSIMAT learning model is highly valid, with a score of 91.6%, and include minor suggestions, such as the addition of visual illustrations and interactive examples. Keywords: child psychology, disaster emergency response, geometry, gratitude activities, learning model